Antibiotic Resistance of Escherichia coli and Staphylococcus aureus Bacteria in Goats in Pematang Gajah, Jambi - Dedi Damhuri; Yatno Yatno; Asri Rizky; Jessica Anggun Safitri; Ahmad Syarifuddin (Jurnal Biologi Tropis, 2026)
Limited knowledge among smallholder goat farmers regarding appropriate antibiotic use may contribute to the emergence of antimicrobial resistance in livestock-associated bacteria. This study aimed to identify bacterial isolates and evaluate antibiotic resistance patterns of bacteria obtained from fecal and nasal mucosal swabs of goats in Pematang Gajah. Samples were collected from nine goats with three repeated examinations. Bacterial identification was performed using Gram staining followed by standard biochemical tests. The results showed that 8 of 9 isolates (≈90%) from fecal swabs exhibited biochemical characteristics consistent with Escherichia coli, including Indole (+), MR (+), VP (−), Citrate (−), TSIA A/A with gas production, positive motility, and metallic green sheen on EMB agar. A total of 7 of 9 isolates (≈76%) from nasal mucosal swabs demonstrated typical characteristics of Staphylococcus aureus, namely Gram-positive cocci, catalase-positive, coagulase-positive, mannitol fermentation positive, and β-hemolysis. Antibiotic susceptibility testing conducted on one isolate of E. coli and one isolate of S. aureus with three replications revealed the highest inhibition zones in E. coli against enrofloxacin (23.33 ± 0.58 mm) and gentamicin (21.33 ± 0.58 mm), categorized as sensitive, while high resistance was observed against tylosin (8.33 ± 0.58 mm) and penicillin–streptomycin (9.33 ± 0.58 mm). Staphylococcus aureus isolates showed high sensitivity to enrofloxacin (24.33 ± 0.58 mm), tylosin and gentamicin (22.33 ± 0.58 mm), but resistance to penicillin–streptomycin and ampicillin. These findings indicate variability in antimicrobial susceptibility among goat-associated bacteria and highlight the importance of susceptibility-based antibiotic selection to reduce antimicrobial resistance risk.